DUCTILITY EVALUATION OF REINFORCED CONCRETE COLUMN MADE OF NORMAL- TO HIGH-STRENGTH CONCRETE UNDER CONSTANT AXIAL LOAD LEVEL COMBINED WITH FLEXURAL LOADING USING NONLINEAR SECTIONAL FIBER BASED MODEL - Bambang Piscesa; Dwi Prasetya; Mudji Irmawan; Harun Alrasyid (Institut Teknologi Sepuluh Nopember (ITS), 2019)
This study presents the ductility evaluation of reinforced concrete column made of normal-strength material using various empirical stress-strain model with nonlinear sectional fiber based analysis. The purpose is to evaluate the confinement requirement for reinforced concrete column under high axial load level. The concrete strength considered in the analysis are varies from 30 to 70 MPa while the steel reinforcing bar yield strength considered is only 400 MPa. The ductility is evaluated by using the customized ductility index measurement. The ratio of the concrete cover to the concrete core is set to 0.1 but not more than 40 mm. Attard and Setunge’s concrete constitutive model is used in this investigation. Cover spalling behavior is considered in the analysis by including the restrained shrinkage effect on the concrete strength and the softening behavior. From this study, it was found that extra confinement is necessary to maintain the expected minimum level of ductility.